Placemaking in Area C The Forgotten Village (Yanoun) - Aburas, Hala (My University, 2017)
The Israeli Occupation is the main reason up to date that inflect adversely the daily life of Palestinians. However, the struggle and the patience, which is well known, feature of Palestinians help them so much to stand still over all difficulties. When you look around you see many people forced to leave their homes, which was big chance for settlers to take all of their stuff. The methodology of the study is based on the case study approach. A live example for the Israeli policy for stealing the best areas of Palestine. It is about Palestinian village called Yanoun, which is almost empty and surrounded allover by settlers. The aim of the study is to find all possible solutions to enhance the steadiness of people who are living there and encourage people to come back and live there to establish all abilities in order to keep Yanoun live again